2013
DOI: 10.1089/vbz.2012.0982
|View full text |Cite
|
Sign up to set email alerts
|

Oral Receptivity ofAedes aegyptifrom Cape Verde for Yellow Fever, Dengue, and Chikungunya Viruses

Abstract: At the end of 2009, 21,313 cases of dengue-3 virus (DENV-3) were reported in the islands of Cape Verde, an archipelago located in the Atlantic Ocean 570 km from the coast of western Africa. It was the first dengue outbreak ever reported in Cape Verde. Mosquitoes collected in July 2010 in the city of Praia, on the island of Santiago, were identified morphologically as Aedes aegypti formosus. Using experimental oral infections, we found that this vector showed a moderate ability to transmit the epidemic dengue-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
6
33
0
Order By: Relevance
“…This strain was the only one potentially transmitted at 5 dpi with rates ranging from 33% to 100%. The same trend was shown in a previous study 26 ; Cape Verde Ae. aegypti dissemination rates of an ECSA CHIKV strain were 91-100% depending on the EIP.…”
Section: -10supporting
confidence: 91%
See 3 more Smart Citations
“…This strain was the only one potentially transmitted at 5 dpi with rates ranging from 33% to 100%. The same trend was shown in a previous study 26 ; Cape Verde Ae. aegypti dissemination rates of an ECSA CHIKV strain were 91-100% depending on the EIP.…”
Section: -10supporting
confidence: 91%
“…aegypti populations from Cape Verde, the CHIKV isolate used was from La Réunion Island, including A226V substitution in the envelope protein E1. 26 For mosquito populations from Senegal, despite their frequent associations with CHIKV in nature, vector competence studies have never been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The salivary gland lobes are surrounded by the salivary gland basal lamina, which forms a physical barrier to virus infection of the salivary gland epithelial cells (da Cunha Sais et al 2003, Franz et al 2015, Romoser et al 2005. Although less profound than the midgut barrier, the presence of a salivary gland entry barrier has been reported for several flaviviruses in both Aedes and Culex mosquitoes , Turell et al 2006, Vazeille et al 2013. Both the mechanical and the molecular nature of the salivary gland infection and escape barriers have not completely been defined.…”
Section: Mosquito Barriers To Arbovirus Infection and Transmissionmentioning
confidence: 99%